PENERAPAN PEMBELAJARAN METODE LATIHAN UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VI SD NEGERI 007 KAMPUNG BARU KECAMATAN UKUI - Ayi Saepudin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Based on the results of tests conducted on social studies student learning results obtained arelow, the researchers observed that in general the students have not reached the limit ofmastery learning expected by SBC. Students who reach KKM on the subjects of socialsciences with KKM 65 only 10 (50%) of 20 students. Furthermore, the low student learningoutcomes occurred is also due in teaching subjects the researcher as a teacher gives lessvariation and implementing teaching methods that can make students feel happy and makeactive students become more active and creative in learning which in turn student learningoutcomes low, This research forms a classroom action research. Classroom action researchis one of the efforts of teachers in the form of various activities undertaken to improve or toimprove the quality of learning in the classroom. From the research data result of learningIPS above can be seen yield increases social studies students from the action on thepreliminary data for the first cycle to the second cycle by improving student learningoutcomes that menigkat are significant, the initial data of students who achieve mastery only50% and in I cycle to the increase has reached 70% and the thoroughness of the class in thesecond cycle reaches 80% of the 20 students of grade VI SD Negeri 007 Kampung Baru